A104 ASSOCIATION BETWEEN THE DIETARY INFLAMMATORY INDEX AND HIGH FECAL CALPROTECTIN IN ULCERATIVE COLITIS PATIENTS - Keshteli, A H (J Can Assoc Gastroenterol, 2019)
BACKGROUND: The association between diet and inflammatory bowel disease remains largely unknown. To date, few studies have been conducted to investigate the association between the inflammatory potential of a diet and disease activity in patients with inflammatory bowel disease. AIMS: We conducted this study to evaluate the relationship between dietary inflammatory index (DII) and fecal calprotectin (FCP) levels in a cohort of ulcerative colitis (UC) patients. METHODS: This was a cross-sectional study on adult UC patients who were in clinical remission (partial Mayo<3). Dietary intake in the past year was assessed using a validated self-administered food frequency questionnaire (Diet History Questionnaire II). Intake of 29 macro- and micronutrients as well as caffeine was used to calculate total DII score (minimum score: -3.6 maximum score:3.5). A greater DII was indicative of a more pro-inflammatory diet. FCP was measured using ELISA. FCP >250 µg/g which is associated with higher disease activity and increased probability of UC relapse was considered as high. RESULTS: Fifty-nine UC patients were recruited. Their mean age was 40.3 ± 14.2 years and 61% of them were females. Their mean DII score was -0.3 ± 1.9. Patients with high FCP had higher DII scores than patients with low FCP (0.8 ± 1.7 vs. -0.8 ± 1.8, P=0.004). UC patients with a more pro-inflammatory diet (DII score > -0.5 (median value)) were more likely to have high fecal calprotectin in comparison to patients with a less pro-inflammatory diet (44.8 vs. 16.7%, P=0.02, Odds ratio: 4.1, 95% confidence interval: 1.2–13.6). In addition, Spearman analysis suggested a significant correlation between FCP and DII scores (r=0.35, P=0.007). Among different components of DII, FCP was correlated significantly with dietary intake of alcohol (r= -0.29), β-Carotene (r= -0.44), fiber (r= -0.23), polyunsaturated fatty acids (r= -0.22), and vitamin E (r= -0.42). CONCLUSIONS: We found that a pro-inflammatory diet was related to increased FCP in UC patients. These findings suggest that an association between diet and increased disease activity or relapse might be mediated through inflammatory properties of the diet. FUNDING AGENCIES: Alberta Innovates - Bio Solutions